Clean and healthy living culture education to protect the students from Covid-19 in senior high school of Muhammadiyah II, Beji, Depok - Untari, Sri Isti; Praptiwi, Rahma Nur; Rahmi, Iftita; Ariyanti, Tika Dwi (Universitas Muhammadiyah Magelang, 2021)
At the end of 2019 the world's population was tested by the presence of the Covid-19 virus, which in a short time was classified as a pandemic by the World Health Organization (WHO). Millions of people have been affected by the infection and also tens of thousands have died. One of the preventions of transmission of the Covid-19 virus is by implementing a culture of clean living and implementing strict health protocols. Meanwhile, the fact is that the implementation of a culture awareness of clean living and health protocols is still low. The purpose of this activity is to provide knowledge of senior high school of Muhammadiyah II Beji-Depok students about clean and healthy living habits and also to provide assistance in adding hand washing and ablution facilities. This community service activity was carried out face-to-face and was carried out from August to December 2020. The result of this activity was the implementation of socialization related to the culture of clean living, giving free masks, and the construction of hand washing facilities.